(untitled) (Nepal Agriculture Research Journal, 2009)
A field experiment was conducted at the agro-ecological research site (AER site) of the Regional Agriculture Regional Station, Lumle, at Deurali in Palpa (1200 masl) during rainy season of 2004 and 2005. The main objective of the experiment was to evaluate the different varieties of onion and their transplanting time for off-season production in mid hill conditions. Treatments were four onion varieties, namely LR-241, N-53, Nasik Red and Red Creole and four transplanting dates as 25 July, 5 August, 15 August, and 25 August. The trial was conducted in RCBD with factorial arrangement of treatments and replicated three times considering farmer as a replication. The plot size was maintained 1.4 m2 (1.4 x 1 m2). Observation was recorded on plant height, plant stand at maturity, diameter and length of bulbs, neck thickness and yield of green bulbs and green tops. The varieties showed a significant different only on the fresh bulb production. Transplanting dates showed a significant difference on the plant height, plant stand at maturity and marketable bulb production. The highest fresh bulb yield (16.63 t ha-1) observed on the variety N-53. Similarly, August 15 transplanting date produced the highest bulb yield (15.31 t ha-1) among four transplanting dates. This novel technology for off-season onion bulb production through seedlings would be good opportunity for increasing the income of many hill farmers which have no access to low land and irrigation facility during normal onion production season. The production of green tops in this period is consumable and easily saleable in the local market. So farmers get extra income from this technology. Key words: Bulb yield; off-season onion; transplanting date; varieties DOI: 10.3126/narj.v7i0.1862 Nepal Agriculture Research Journal Vol.7 2006 pp.21-26